2020
DOI: 10.3390/jcm9061785
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Antioxidant Biomarkers and Their Correlation with Clinical Condition and Lifestyle with Regard to Male Reproductive Potential

Abstract: Measurement of sperm oxidative-antioxidant indicators is widely used in the assessment and detection of biochemical causes of male infertility. The main purpose of this study was to identify biomarkers that assist in diagnostics and monitoring of male reproductive potential. We performed the assessment of oxidative-antioxidant malondialdehyde (MDA), glutathione (GSH), and total redox antioxidant potential (TRAP) indicators in seminal plasma, seminogram, clinical condition, and lifestyle of people with reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…According to modern ideas, the development of pathological processes in the body, in particular caused by microorganisms, is accompanied by a violation of the mechanisms of antioxidant protection of cells Aitken, 2020;Yin et al, 2020). The obtained data to some extent agree with others where the increase of MDA level and decrease of concentration of reduced glutathione in seminal plasma at azoospermia is shown (Krzysciak et al, 2020;Kurkowska et al, 2020). The obtained data are to some extent consistent with others where an increase in the MDA level and a decrease in the concentration of reduced glutathione in seminal plasma in azoospermia (N' Guessan at al., 2016;Sinha & Gupta, 2018) and impaired expression of the glutathione transferase gene family are associated with the development of male infertility (Fafula et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…According to modern ideas, the development of pathological processes in the body, in particular caused by microorganisms, is accompanied by a violation of the mechanisms of antioxidant protection of cells Aitken, 2020;Yin et al, 2020). The obtained data to some extent agree with others where the increase of MDA level and decrease of concentration of reduced glutathione in seminal plasma at azoospermia is shown (Krzysciak et al, 2020;Kurkowska et al, 2020). The obtained data are to some extent consistent with others where an increase in the MDA level and a decrease in the concentration of reduced glutathione in seminal plasma in azoospermia (N' Guessan at al., 2016;Sinha & Gupta, 2018) and impaired expression of the glutathione transferase gene family are associated with the development of male infertility (Fafula et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…For this purpose, Krzyściak et al [24] highlighted the importance of using the combination of oxidative-antioxidant markers as potential predictors of male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of sperm cells to oxidative damage is a result of their enrichment with unsaturated fatty acids within sperm plasma membrane. 31 Sanocka and Kurpisz, 2004 32 revealed that increased lipid peroxidation leads to oxidative damage to sperm DNA, modification of membrane function, impairment of mobility, and a possiblly significant effect on spermatogenesis. 29 Lipid peroxidation is one of the major processes in oxidative damage, 33 and this was assessed in this study by the measurement of TBA-reactive substances, particularly MDA.…”
Section: Discussionmentioning
confidence: 99%